Predicting Gen Z’s Sentiments on Gorontalo’s CulturalWisdom UsingSentiment Analysis Models - Hermila A.; Rahmat Taufik R. L Bau; Sitti Suhada; Abdulaziz Ahmed siyad (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
In the digital era, Generation Z faces both opportunities and challenges in understanding and preserving local cultural wisdom. It is essential to ensure that cultural values go beyond superficial consumption in cyberspace and remain deeply valued as integral aspects of identity and history. As technological advances and globalization continue influencing young people to preserve, local culture presents an increasing challenge. This study aims to determine Generation Z’s perceptions of Gorontalo’s local cultural wisdom, focusing on the Dikili and Meeraji traditions through a sentiment analysis approach. This research method uses the Naive Bayes algorithm to analyze positive, negative, and neutral sentiments derived from text data processed through a structured pre-processing stage. The findings reveal that Generation Z’s perceptions of the Dikili and Meeraji cultures are mostly positive, reflecting a strong appreciation and acceptance of these cultural values. However, the presence of negative sentiment highlights a critical view among some members of Generation Z, who consider certain aspects of these traditions less relevant or controversial in a modern context. In addition, neutral sentiment indicates a segment of young people who may need more exposure or information to form an informed opinion. The study concludes that while Dikili and Meeraji cultures still hold value among Generation Z, a more inclusive and adaptive approach to cultural preservation is needed. The findings offer valuable insights for strategies to preserve and develop local cultural heritage in the digital age.